الصّفة المشبّهة: دراسة صرفية نحوية تحليليّة: الصّفة المشبّهة، دراسة، صرفيّة، ونحويّة - Ø´Ø¹Ø¨Ø§Ù†, Ø¥Ø¨Ø±Ø§Ù‡ÙŠÙ…; ÙØ§, Ù…Øª Ø·ÙŠØ¨; ØµÙØ±, Ø£ØÙ…Ø¯ Ø¹Ø§Ø±ÙÙŠÙ† (Al-Ḍād Journal, 2018)
This paper is a desk study of the morphological and grammatical analysis about “الصّفة المشبّهة - the attributive participle”, and is carried out on the basis of comprehensive research from reliable Arabic language references and from thorough investigations of Arabic linguistics, and also finding out authentic examples from sources of Arabic language such as the holy Quran, the glorious Hadith, poems and Arabic write-ups. The paper also focusses on definitions, types, scales and rules of attributive participle. The outcomes from this paper is to comprehend the different definitions of attributive participle based on the unanimous and un-unanimous consensus by the Arabic linguistics and the stands given by Sibawayh, in which it can be used as masculine, feminine and can be definite by Arabic “Alif-and-Laam”, similarly, it can be ‘Muthanna’ dual and sound plural. Moreover, the relationship between “attributive participle” and “present participle” and its closeness sound with present tense “Al-Fi’il almudhari”can vividly be known. In conclusion, the unanimous and un-unanimous consensus by the Arabic linguistic about the object of attributive participle can be known, and these has been carried out in a way that simplify the understanding of the morphological and grammatical rules to the students of Arabic language.